Novel Perspectives in Quantum Safe Crypto algorithms for Enhanced Cyber Security - Manas Kumar Yogi; Yamuna Mundru (International Journal of Computer Science Languages, 2023)
This paper explores novel perspectives in quantum-safe cryptographic algorithms to bolster cybersecurity in the face of impending quantum computing advancements. Due to the efficient resolution of intricate mathematical problems by quantum computers, posing a substantial threat to existing cryptographic systems, there is a pressing requirement to create resilient alternatives. This study delves into innovative approaches, drawing from quantum-resistant cryptographic primitives, lattice-based cryptography, code-based cryptography, and hash-based cryptography. By examining the strengths and vulnerabilities of these methods, the research aims to provide a comprehensive understanding of their applicability in real-world scenarios. Furthermore, the study investigates the integration of quantum-safe algorithms into existing systems, considering factors such as performance, scalability, and compatibility. The research contributes to the evolving landscape of cybersecurity by proposing practical solutions that address the imminent quantum threat. The findings have broad implications for industries, governments, and individuals reliant on secure communication and data protection, offering a roadmap for transitioning towards quantum-safe cryptographic infrastructures. Ultimately, this research seeks to advance the discourse on quantum-resistant cryptography, fostering a more secure digital environment in the era of quantum computing.
Keywords: Cryptography; Cybersecurity; Privacy; attack; quantum